2009
DOI: 10.1182/blood-2009-06-227330
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled clinical trial of ketoprofen for sickle-cell disease vaso-occlusive crises in adults

Abstract: Vaso-occlusive crisis (VOC) is the primary cause of hospitalization of patients with sickle-cell disease. Treatment mainly consists of intravenous morphine, which has many dose-related side effects. Nonsteroidal antiinflammatory drugs have been proposed to provide pain relief and decrease the need for opioids. Nevertheless, only a few underpowered trials of nonsteroidal antiinflammatory drugs for sickle-cell VOC have been conducted, and conflicting results were reported. We conducted a phase 3, double-blind, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
1
32
0
2
Order By: Relevance
“…Furthermore, our study results indicated high ACS frequency during DHTR, estimated at 50%, while only 20% of VOC suffers developed secondary ACS. 18 The extent of intravascular hemolysis in severe DHTR could partly explain the vascular reaction leading to ACS. Indeed, physiological findings demonstrated that cell-free plasma Hb was associated with endothelial dysfunction and PHT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our study results indicated high ACS frequency during DHTR, estimated at 50%, while only 20% of VOC suffers developed secondary ACS. 18 The extent of intravascular hemolysis in severe DHTR could partly explain the vascular reaction leading to ACS. Indeed, physiological findings demonstrated that cell-free plasma Hb was associated with endothelial dysfunction and PHT.…”
Section: Discussionmentioning
confidence: 99%
“…VOC was defined as pain, affecting at least one part of the body, including limbs, ribs, sternum, head (skull), spine, and/or pelvis, which required antalgics and was not attributable to other causes. 18 The diagnosis of ACS was based on the association of a respiratory symptom (dyspnea or chest pain), an abnormal lung sound at auscultation, and a new pulmonary infiltrate on the chest radiograph. In some cases, we have jointly used the rate of decline in hemoglobin (HbA)…”
Section: Methodsmentioning
confidence: 99%
“…The primary endpoint was ACS onset within 15 days of admission, defined as the appearance of an auscultatory abnormality (crepitants and/or bronchial breathing) and/or chest pain and an infiltrate on chest film and/or thoracic computed-tomography (CT) scan but excluding atelectasia. Secondary endpoints were: hospitalization duration, BT, morphine consumption, visual analog scale (VAS: 0 mm, none; 100 mm, worst possible) for pain and our categorical pain score (CPS: range 0–3 points: 0, no pain; 1, mild pain, unaffected by mobilization; 2, moderate pain, increased by mobilization; 3, severe pain with disability) (Bartolucci et al, 2009) evaluations, BT, intensive care unit admission and mortality. Medical history and precipitating factors were systematically recorded on a standardized form.…”
Section: Methodsmentioning
confidence: 99%
“…Le nefopam est quelque fois utilisé en association avec ces deux drogues. Les benzodiazépines ne sont pas recommandées dans ce contexte aigu en raison de leurs effets centraux associés aux morphiniques et les anti-inflammatoires non stéroï-diens n'ont pas montré d'intérêt en association systématique avec les morphiniques dans le contrôle des douleurs des crises vaso-occlusives [19]. Le protoxyde d'azote et, dans des cas exceptionnels la kétamine, peuvent être utilisés comme appoint dans les crises hyperalgiques.…”
Section: Prise En Chargeunclassified